2020
DOI: 10.2147/prbm.s276448
|View full text |Cite
|
Sign up to set email alerts
|

<p>Do Medical Students Experience Writing Anxiety While Learning English as a Foreign Language?</p>

Abstract: Aim The study examines English Foreign Language (EFL) writing anxiety among medical students in terms of the levels, types, and causes of writing anxiety. Methods This study is a cross-sectional study consisting of 684 first-year medical students from Jordanian universities. The participants responded to an online survey consists of Second Language Writing Anxiety Inventory (SLWAI) and Causes of Writing Anxiety Inventory (CWAI), 15 of whom were invited for semi-structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 41 publications
5
14
0
Order By: Relevance
“…They are also concerned about how their compositions would be received by the readers, and that their teacher may use their writing output as a sample to be discussed in the class. This is consistent with the results of a study by Rabadi & Rabadi (2020), wherein it was determined that the root cause of English language learners' writing anxiety is their poor linguistic knowledge. Students who have limited knowledge of grammatical rules and have poor vocabulary experience high levels of writing anxiety.…”
Section: Resultssupporting
confidence: 91%
“…They are also concerned about how their compositions would be received by the readers, and that their teacher may use their writing output as a sample to be discussed in the class. This is consistent with the results of a study by Rabadi & Rabadi (2020), wherein it was determined that the root cause of English language learners' writing anxiety is their poor linguistic knowledge. Students who have limited knowledge of grammatical rules and have poor vocabulary experience high levels of writing anxiety.…”
Section: Resultssupporting
confidence: 91%
“…The results of this study are in agreement with the results of the previous studies [17]. Conversely, the findings of this study are different from studies that found most students were highly anxious in writing activity [16], [30]. Concerning gender analysis, this study supports the finding of studies ( [1], [21], [22] which show that male students were less anxious than female students, but they were not significantly different [23], [31].…”
Section: Discussionsupporting
confidence: 87%
“…While the students were found to experience cognitive anxiety as their most dominant type of writing anxiety, the results were quite predictable, which was also seen in (Kusumaningputri et al, 2018;Okubay, 2020;Rabadi and Rabadi, 2020). The students may not set the target of getting excellent marks, but the effect of cognitive anxiety could drive learners to worry about negative evaluation of their work (David et al, 2018;Tsiriotakis et al, 2017).…”
Section: Discussionmentioning
confidence: 83%
“…In line with the review of the related studies, much research has been carried out to determine the types, levels, and causes of ESL writing anxiety. The findings differ from one another, such as in some studies, the most dominant type of writing anxiety is cognitive anxiety (David et al, 2018;Iksan & Halim, 2018;Jafari, 2019;Kusumaningputri et al, 2018;Okubay, 2020;Rabadi & Rabadi, 2020;Tsiriotakis et al, 2017;Wern & Rahmat, 2021). As for somatic anxiety, it is found to be the most dominant in some research, such as in (Alfiansyah et al, 2017;Arindra and Ardi, 2020;Ekmekci, 2018;Rudiyanto, 2017).…”
Section: Previous Studies On Esl Writing Anxietymentioning
confidence: 90%